Boiled Milk Anne Brontë's Final Journey - Stewart, Michael (University of Huddersfield Press, 2020)
This book is a special collectors' edition of a forthcoming chapter from Walking the Invisible: The Brontës' Lives and Landscapes, Then and Now, which will be published by HarperCollins in hardback in July 2021. A limited number of 200 copies have been published, signed and numbered, to celebrate 200 years since the birth of Anne Brontë.